Analysis of intraoperative microscopy imaging techniques and their future applications - Zhan, Huiling; Sun, Caihong; Xu, Mingyu; Luo, Tianyi; Wang, Guangxing; Xi, Gangqin; Liu, Zhiyi; Zhuo, Shuangmu (Frontiers in Physics, 2022)
During tumor resection, doctors use intraoperative biopsies to determine the tumor margin. However, the pathological procedures of traditional diagnostic methods, such as imprint cytology and frozen section analysis, are complicated and time-consuming. As this is not conducive to surgeries, their applications are limited to a large extent. Therefore, novel fast microscopy imaging technologies with resolutions comparable to those of pathological tissue sections are necessary. Stimulated Raman scattering (SRS), photoacoustic microscopy (PAM), multiphoton microscopy (MPM), and optical coherence microscopy (OCM) exhibit the advantages of high spatial resolution, large imaging depth, avoiding damage to biological tissues, label-free detection, and the availability of biochemical information of tissues. Additionally, they are superior to intraoperative biopsies owing to their fast imaging speeds. Therefore, they possess broad application prospects in tumor resection surgeries and the diagnosis of other diseases. This study briefly introduces the basic principles, structural characteristics, advantages and disadvantages, and the existing research status of SRS, PAM, MPM, and OCM in biomedicine. Furthermore, we propose a multi-mode hybrid detection technology that can be used for surgeries. The combination of the proposed technology with deep learning-based artificial intelligence can form the basis for intraoperative diagnosis in the future.